The Influence of Online Promotion, Trust, and Website Quality on Online Impulsive Purchases as well as Emotional Responses to Online Impulsive - Sulaiman, Muhammad; Suripto, Suripto; Agung P, Maulana; Wardianto, K Bagus (Universitas Indo Global Mandiri Palembang, 2025)
Objective; This study aims to determine the impact of online promotions, trust, and website quality on online impulsive purchases, as well as to examine consumers' emotional responses after making online impulsive purchases. Methods; It specifically investigates the influence of online impulsive purchases on both positive and negative emotions. This study used an explanatory method with a quantitative approach. Originality/Value;Furthermore, the samples were 100 consumers of the Shopee Marketplace located in Lampung Province, Indonesia. The data were obtained through a questionnaire and analyzed using descriptive statistics and Partial Least Squares (PLS) analysis. Findings; The results showed online promotions and website quality had a significant influence on online impulsive purchases, while trust had no significant influence. Also, online impulsive purchases were found to have a significant influence on positive emotions, but no significant influence on negative emotions. Practical/Policy implication: Research shows that engaging online promotions and a high-quality website can encourage impulse buying, which is driven by emotions and situations, not beliefs. Impulse buying also increases positive emotions, so marketing strategies that stimulate it have the potential to increase customer satisfaction and loyalty.